Understanding consumer adoption of QR-code based e-wallet services: an extended UTAUT 2 approach / Faten Aisyah Ahmad Ramli - Ahmad Ramli, Faten Aisyah (2021)
Worldwide trend brings Malaysia to move forward and change itself to become cashless society by 2050. Malaysians have witnessed the proliferation of electronic wallet (E-wallet) where it already takes place in digital payment platforms over past few years. Many local and international players have set foot in Malaysian market such as Boost, GrabPay, WechatPay, and Touch n Go. However, e-wallet in Malaysia somehow is still not on their right track. Thus, this study is conducted to provide insight on this issue and narrowing the gap of previous studies by focusing on QR-code based e-wallet services. A conceptual framework is formed to evaluate the relationships between UTAUT 2 dimensions and Usage Intention. The moderating effects of Consumer-Based Brand Equity constructs on these relationships are also analysed. The minimum sample size was set at 249 by employing Gpower software. Non-probability sampling was selected by the researcher, particularly purposive sampling. This study analysed the data gathered by using the latest version of SPSS. The findings involving 305 respondents across Central Klang Valley provide verification for validity and reliability. The results on the direct relationships depict that only three direct relationships between UTAUT 2 and usage intention are found to be significant namely Effort Expectancy, Social Influence and Price Value. Meanwhile, the results had indicated, only Brand Image has positive and significant interaction effect on the link between Price Value and intention to use QR-code based E-wallet in Malaysia. Hence, this study makes contributions to the current literature by employing UTAUT 2 as the predictors of usage intention with the moderating impact of Brand Awareness, Brand Image, and Perceived Quality. Discussions on theoretical and practical contributions were provided to aid future study in this field.